2002
DOI: 10.1021/jp0121116
|View full text |Cite
|
Sign up to set email alerts
|

Study of Preferential Solvation in Mixed Binary Solvent as a Function of Solvent Composition and Temperature by UV−Vis Spectroscopic Method

Abstract: Preferential solvation of N-ethyl-4-cyanopyridinium iodide and 2,6-diphenyl-4(2,4,6-triphenyl-1-pyridino)phenolate [Reichardt's ET(30) dye] has been studied in ethanol + tetrahydrofuran, ethanol + acetonitrile and acetonitrile + tetrahydrofuran binary mixtures as a function of temperature and composition of mixed binary solvents. It has been found that besides solute−solvent interaction, solvent−solvent interaction plays an important role in determining the solvation characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
(41 reference statements)
0
29
0
1
Order By: Relevance
“…In our studies with binary solvent mixtures, it has been noted that electron spectroscopic studies provide a method for the estimation of K 12 . 15 It has also been found that K 12 values for binary solvent mixtures are smooth functions of the ratio of the mole fractions of the solvent components, x 1 /x 2 . Figure 3 shows the representative plots indicating composition dependence of K 12 for binary mixtures.…”
Section: Discussionmentioning
confidence: 97%
“…In our studies with binary solvent mixtures, it has been noted that electron spectroscopic studies provide a method for the estimation of K 12 . 15 It has also been found that K 12 values for binary solvent mixtures are smooth functions of the ratio of the mole fractions of the solvent components, x 1 /x 2 . Figure 3 shows the representative plots indicating composition dependence of K 12 for binary mixtures.…”
Section: Discussionmentioning
confidence: 97%
“…The binary solvent mixture is considered to be ideal, when the absorption energy at the maximum absorbance, is a linear combination of the absorption energy at the maximum absorbance in pure solvent, weighted by their mole fraction in the solvent mixture. This is given by eqn (3) . Elinear,4ptbulk is the absorption energy at the maximum absorbance in an ideal solvent mixture. trueElinear,bulk=xnEn+xpEp4pt …”
Section: Theorymentioning
confidence: 99%
“…The change in the absorption maxima for different composition has been analysed with the help of approach used by Kauffman et al . and other recent studies . At lower mole fraction of alcohol, PNA shows synergistic solvation behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the importance of studying binary (and higher order) solvent systems is obvious. A major question which comes up in these studies is to what extent is there preferential solvation by one of the solvents, which can be related to the specific solute-solvent and solvent-solvent 1 interactions as well as dipole-dipole interactions, the latter being quite general. These are measured most often by plotting curves of some spectroscopic 2 property (maximum wavelength, peak height, etc.)…”
Section: Introductionmentioning
confidence: 99%